A lithium air battery with a lithiated Al–carbon anode. Issue 4 (21st November 2014) - Guo, Ziyang; Dong, XiaoLi; Wang, Yonggang; Xia, Yongyao
Abstract : A lithiated Al–carbon electrode was coupled with an O2 catalytic electrode to form a rechargeable Li–O2 (or air) battery. Abstract : A lithiated Al–carbon composite electrode with a uniform SEI film was prepared by an electrochemical method, and was then coupled with an O2 catalytic electrode to form a rechargeable Li–O2 (or air) battery with a Li x Al–C anode.